Influences of helicid on metabolism of four amino acids in the brain and synaptosomes in mice - Zhou Xi; Zhao Tian-Rui; Nan Guo-Hua; Li Jian-Yi (Acta Pharmacologica Sinica, 2016)
After iv helicid (Hel) 120 mg/kg, the contents of GABA, Asp and Glu in the brain and synaptosomes of normal mice were unchanged, but the level of Gin in the brain was reduced and the ratio of GABA/Glu was raised. The descent of the contents of GABA in the brain and synaptosomes and the ascent of the contents of Glu and Asp in synaptosomes elicited by thiosemicarbazide all returned to normal. A fall in the activity of glutamine synthetase and a rise of that of GPT were observed, but on those of GOT and glutaminase no effects were seen. The influences of Hel on the metabolism of these amino acids may relate to its maintenance of the excitoinhibitory balance of CNS.